PENGARUH PENDIDIKAN DAN PELATIHAN TERHADAP EFEKTIVITAS PENGGUNAAN SISTEM INFORMASI AKUNTANSI - Anggita, Ni Wayan Nonik; Suartana, I Wayan (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2022)
This study aims to determine the effect of education and training on the effectiveness of the use of accounting information systems by conducting empirical testing. This research was conducted in Village Owned Enterprises (BUM Desa) throughout Payangan District. The entire population was used as the research sample, as many as 36 people. Data was collected by distributing questionnaires. The data analysis technique used is multiple linear regression analysis. The results showed that education had no effect on the effectiveness of using AIS. On the other hand, training has a positive and significant effect on the effectiveness of using AIS. It is recommended for Village Owned Enterprises in Payangan District to focus more on increasing the effectiveness of the use of technology-based accounting information systems by improving the quality of human resources by providing more training on the use of technology-based accounting information systems, especially for BUM Desa which has just implemented a technology-based information system.